Survei Rumah Tangga terhadap Profil Obat pada Responden dengan Jaminan Kesehatan Nasional di Jakarta Timur - Restinia, Mita; Anggriani, Yusi; Khairani, Sondang; Wijaya, Rulliani Bianca (JSFK (Jurnal Sains Farmasi & Klinis), 2020)
Household surveys are one of the methods to obtain accurate information on medicine utilization in society. The study was carried out to identify the access of medicine and medicine utilization profile. A survey using convenient sampling method was conducted in 30 households with national health insurance (JKN) diagnosed with chronic diseases in East Jakarta. Each family was observed once a week for 8 weeks to analyse their diseases, medication used, and medicine access. About 19 (63.3%) respondents enrolled in this study were male. The mean Â± SD of age was 55.87Â±12.486 years old. About 23(76.7%) respondent had access of medicine through hospital and 7(23.3%) by pharmacy directly. The most common chronic diseases identified were cardiovascular and endocrine disorder. Cardiovascular, alimentary tract and metabolism, and nervous system were medications most commonly used. Most of respondents used about 1-3 kind of medications in a month. About 101 kind of drugs used, 74 kinds of drug among of them were generic and 27 were non generic. About 12 (40%) respondents used vitamin and 8 (26.67%) used supplement. This study highlights respondent access of medicine through hospital and cardiovascular medicines were the most commonly used.